The arts in Africa, the visual and the aural - Tracey, Hugh (International Library of African Music, 1962)
For the purposes of this paper the title "The Arts in Africa" is interpreted as the Arts of indigenous Africans only. Of all the people living south of the Sahara, over eighty per cent, four out of every five persons, still live in the country and not in towns or industrial areas. Consequently, about four-fifths of all African arts can still be classed as rural. As with folk arts the world over, African rural arts play an important part in creating public opinion and upholding social disciplines. The arts of the urban minority cannot yet be considered to be the "norm" but rather the "abnorm", and should be treated separately. Unlike their rural relatives, African town dwellers enjoy a highly disorganised social and ''family" life, regardless of the nature of local political control, either indigenous or expatriot. Sociologists have found for example that the various anti-social activities of both Negroes and Africans are equally high in places as diverse and as far apart as the island of Jamaica, Accra, Lagos, Kampala, and Johannesburg. Urban arts of the present day do not yet have the same integrating effect upon African social life as the rural. In normal circumstances, Whites throughout Africa appear to prefer various aspects of the urban arts which are closest to them and which they find entertaining. They tend to encourage, almost exclusively, imitation of Western urban habits and recreations. They have not as a rule the slightest contact with African folk arts which are considered by them to be primitive and pre-civilised. This paper should therefore be read in this context.
Keywords: Ethnomusicology; Music; Africa; Arts; Songs; African Music